Research on aging behaviors of insulating silicone oil for cable terminals based on chromatographic and spectroscopic analysis - Wei Zhang; Jie Chen; Chenying Li; Jingying Cao; Xiao Tan; Chao Gao (PLoS ONE, 2025)
With the widespread deployment of high-voltage cable terminals in power systems, insulating silicone oil has become a critical medium due to its superior dielectric and thermal properties. However, conventional diagnostic methods such as the three-ratio gas analysis developed for transformer oil have proven ineffective for silicone oil, owing to its distinct chemical structure and degradation behavior. To address this, this study aims to establish a fault-type identification method specifically for silicone oil to enhance the operational reliability of cable terminals. Accelerated thermal aging experiments (140°C, 30 days) were conducted to simulate long-term aging of silicone oil. By integrating partial discharge, high-energy discharge, and breakdown experiments, the gas generation patterns of silicone oil under different stresses were systematically analyzed. Gas chromatography (GC) and infrared spectroscopy (IR) were employed to track gas composition and chemical structural changes. The results propose the following diagnostic criteria: H₂/CH₄ > 1, C₂H₄/C₂H₆ > 1, and C₂H₂/C₂H₄ < 0.1 indicate overheating faults; H₂/CH₄ < 1, C₂H₄/C₂H₆ < 0.1, and C₂H₂/C₂H₄ < 0.1 correspond to partial discharge; while H₂/CH₄ > 1, C₂H₄/C₂H₆ > 0.1, and C₂H₂/C₂H₄ > 5 signify high-energy discharge. In addition, kinetic modeling based on the Arrhenius equation was applied to extract the activation energy of pyrolytic gas formation, confirming its relation to Si–O bond cleavage. This research provides a foundation for fault diagnosis in silicone oil-insulated equipment, effectively improving the operational reliability of power systems.